Laatokka Suurjärven kiehtova rantahistoria - Lähteenmäki, Maria (Suomalaisen Kirjallisuuden Seuran Toimituksia, 2021)
For the first time worldwide, this collection brings together analyses of the last two centuries of historical change around the shores and drainage basin of Lake Ladoga, Europe's largest lake. The main focus of the narrative is the Northern Ladoga region, which was a Finnish administrative area between 1812 and 1944. After the Second World War, the entire shoreline of Lake Ladoga was incorporated into the northeast part of Russia's border region, the Autonomous Republic of Karelia and the Leningrad Province. The main theme uniting this collection is how the relationship between humans and nature is shaped by industrialization and modernization in society. Other key issues include protecting nature and perspectives on particular places and times, which are reflected in the methodological and thematic choices made in this volume. The research framework set by the editor, Professor Maria Lähteenmäki, is the new lakefront history (Finn. uusi rantahistoria), focusing on approaches to environmental, economic and sensory history of lakes. To draw broad conclusions, on the one hand, the multilevel changes on the lakefront cannot be understood without knowledge of the history of the wider drainage basin, and awareness of the geopolitics of the region and the climate changes. On the other hand, the human relationship to natural waters has changed significantly in 200 years. Thinking in terms of economic benefit has gradually given way to principles of sustainable development. Lake Ladoga is also being redefined from a spatial perspective, as nationalist ownership of the region is coupled with global concern about the state of Europe's largest lake.